A linear numerical model for analysing the hydroelastic response of a flexible electroactive wave energy converter. (October 2017) - Babarit, Aurélien; Singh, Jitendra; Mélis, Cécile; Wattez, Ambroise; Jean, Philippe
Abstract: In this paper, a linear mathematical and numerical model for analysing the dynamic response of a flexible electroactive wave energy converter is described. The Wave Energy Converter (WEC) is a floating elastic tube filled with slightly pressurised sea water. It is made of Electroactive Polymers (EAPs). Under simplifying assumptions, a set of governing equations is formulated for the flow inside the tube, the flow outside the tube and the behaviour of the tube wall. By combining them, the evolution of the flow velocity in the tube can be written as a wave equation. The corresponding eigenmodes of vibration are calculated. Then, using spectral decomposition, the equation of motion for the response of the tube in waves is derived. Experiments were carried out on a scale model of the wave energy converter in the wave tank of Ecole Centrale de Nantes in 2011. Numerical results are compared with experimental results in regular waves, showing rather good agreement, which validates the model and the initial modelling assumptions. Finally, estimates are made for the energy performance of a possible prototype.